APPLICATION OF AN ADAPTATION APPROACH THROUGH NARRATIVE COMPARISONS IN THE NOVEL AND FILM TWILIGHT - Hartati, Yolla Ajeng; Kustanti, Dewi; Permanaludin, Udayani (Universitas Islam Negeri Sunan Gunung Djati, 2024)
In the realm of fine arts, it is common for one form of art to draw inspiration from another, a process known as transformation. This research focuses on the film adaptation of literary works, examining the ecranization of novels into films and the use of adaptation theory to convert novel texts into visual films while preserving the essence of the novel as a hypogram. The study employs a qualitative descriptive method, utilizing close reading and close viewing techniques. It classifies the transformations using Pamusuk Eneste's ecranization (1991) approach and Seymour Chatman's interpretation theory (2018) of the change process in novels and films. The findings reveal that films often include additional stories to convey the setting more explicitly. Although various settings are altered, these changes are justified as it is often impractical to visually depict the atmosphere detailed in the novel. The introduction of new characters in the film aligns with the expanded plot, necessitating the inclusion of characters absent in the novel. Additionally, the visualization of characters in the film undergoes modifications, yet remains consistent with the novel's descriptions. Backgrounds are condensed to fit the film's plot, resulting in the omission of some novel locations in the film adaptation.Keyword: transformation, ecranization, novel, film, twilight